Adaptive cognitive control in 4 to 7-year-old children and potential effects of school-based yoga-mindfulness interventions: an exploratory study in Italy - Toffoli, Lisa; Stefanelli, Giulia; Manca, Giulia; Del Popolo Cristaldi, Fiorella; Duma, Gian Marco; Guidi, Michele; Incagli, Francesca; Sbernini, Luca; Tarantino, Vincenza; Mento, Giovanni (Frontiers in Psychology, 2025)
IntroductionRecent findings showed that adaptive cognitive control (CC) can be instantiated by bottom-up mechanisms, including statistical contingency of event occurrence. However, the developmental evidence in this domain remains limited.MethodsTo address this gap, our study delves into the exploration of different mechanisms underlying adaptive CC in a substantial cohort of young children (211 participants aged between 4 and 7 years). We utilized the Dynamic Temporal Prediction (DTP) task and a modified version of the Flanker task to assess the effect of context predictability on motor preparation/inhibition and interference control, respectively. Furthermore, as part of an exploratory study designed to evaluate the feasibility of a school-based program in Italy, all children underwent a re-testing session after an 8-week intervention involving yoga-mindfulness.ResultsResults suggested that young children can exploit global probabilistic changes to optimize motor preparation/ inhibition while counterbalancing fatigue effects. Moreover, they successfully modulate interference control as a function of environmental contingencies, displaying more optimal conflict resolution when proactive control is engaged. Finally, we observed a post-intervention increase of the capability to implicitly adapt motor preparation/inhibition and a boosting effect on the interference control functions.DiscussionOverall, these findings confirmed that adaptive CC is already present in preschool-aged children, extending these results to include 4-years-olds. Additionally, school-based yoga-mindfulness programs are feasible and might improve children’s capability to flexibly and proactively adapt to environmental requests promoting cognitive proficiency.